How to Create Cutting-Edge Typographic Concepts by Oded Ezer - Panayides, Angelos (My University, 2026)
A short lesson from the "Super Typographer and design fiction hero" as Paola Antonelli from MoMA called him, on how to create and develop experimental works using typography, in order to expand the boundaries of their design profession.